Animal Farm - Orwell, George, 1903-1950 (New Delhi : General Press, 2018)
A satire on totalitarianism features farm animals that overthrow their human owner and set up their own government, only to develop into an equally corrupt society.
Keywords: Domestic animals -- Fiction; Totalitarianism -- Fiction; Political fiction